'There Is No Alternative': Scotland's Curriculum for Excellence and its Relationship with High Culture. Issue 2 (May 2017) - Convery, Alan
Abstract : This article uses the concept of high culture to assess the underlying assumptions and philosophy of Scotland's Curriculum for Excellence (CfE). For the most part, these remain vague and unarticulated. This has two consequences. First, a consensus forms easily around CfE because it means different things to different stakeholders and is presented to teachers as a depoliticised and technocratic policy response. Second, because its core tenets are so hazy, it is extremely difficult to argue against. Although CfE is widely regarded to have at its heart some form of constructivism, the justification for such an approach is never articulated. By assessing CfE's relationship with high culture, this article attempts to flush out its implicit core assumptions. Its central argument is that CfE cannot simultaneously please everyone. Perfectly justifiable alternative curricular paths have been abandoned. Far from being a technocratic and depoliticised policy response, CfE is in fact a much more controversial and ideological shift than the level of scrutiny it has thus far received would suggest.